2018
DOI: 10.1080/19440049.2018.1488183
|View full text |Cite
|
Sign up to set email alerts
|

Game meat consumption by hunters and their relatives: a probabilistic approach

Abstract: This study aimed to estimate the consumption of meat and products derived from hunting by the consumer population and, specifically, by hunters and their relatives. For this purpose, a survey was conducted on the frequency of consuming meat from the four most representative game species in Spain, two of big game, wild boar (Sus scrofa) and red deer (Cervus elaphus), and two of small game, rabbit (Oryctolagus cuniculus) and red partridge (Alectoris rufa), as well as of processed meat products (salami-type sausa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Maximum consumption was by two people who only ate large game meat, so represents an outlying extreme. Sevillano Morales et al (2018) found mean game meat consumption of 8.57 kg/person/year (of wild boar, red deer, rabbit ( Oryctolagus cuniculus ), partridge ( Alectoris rufa ) and processed meat products made from them) in 337 habitual consumers of game (hunters and their relatives).…”
Section: Hazards To Human Health From Ammunition-derived Dietary Leadmentioning
confidence: 99%
“…Maximum consumption was by two people who only ate large game meat, so represents an outlying extreme. Sevillano Morales et al (2018) found mean game meat consumption of 8.57 kg/person/year (of wild boar, red deer, rabbit ( Oryctolagus cuniculus ), partridge ( Alectoris rufa ) and processed meat products made from them) in 337 habitual consumers of game (hunters and their relatives).…”
Section: Hazards To Human Health From Ammunition-derived Dietary Leadmentioning
confidence: 99%
“…In aquatic systems, contaminant concentrations in fish populations are often monitored by state and federal governments, but other game species (such as waterfowl, ungulates, alligators, and rabbits) are typically not given the same level of attention (Conder & Arblaster, 2016 ; Smith et al, 2018 ). Globally, studies have investigated concentrations of contaminants in common game species, many of which have provided information on the risk of consuming game that has been killed with lead bullets and/or game meat that is sourced in close proximity to an area with known contamination (Arioli et al, 2019 ; Fachehoun et al, 2015 ; Morales et al, 2018 ; Oldenkamp et al, 2017 ; Swiergosz et al, 1993 ). While all game species can be exposed to contaminants, long‐lived predatory species living in contaminated environments have the potential to bioaccumulate high‐contaminant body burdens (Rowe, 2008 ), particularly for compounds such as Hg, which tend to biomagnify within an ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Fish and wildlife management professionals use public opinion and attitude surveys to facilitate an understanding of their constituents [36]. Those surveys have been used to consult attitudes towards hunting and fishing [37][38][39], game meat consumption [38,40], or the opinion about governmental wildlife agencies [41]. Public health authorities also use this methodology to obtain information about the food hygiene practices of their citizens [42,43].…”
Section: Introductionmentioning
confidence: 99%